2010
DOI: 10.1111/j.1600-051x.2010.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term benefits of the adjunctive use of metronidazole plus amoxicillin in the microbial profile and in the clinical parameters of subjects with generalized aggressive periodontitis

Abstract: Subjects with GAgP significantly benefit from the adjunctive use of MTZ and AMX. The short-term advantages are observed in the clinical and microbiological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
281
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(310 citation statements)
references
References 49 publications
25
281
2
2
Order By: Relevance
“…The samples were analyzed for 40 oral bacterial species using the Checkerboard DNA-DNA Hybridization technique. 28,29 c. Checkerboard DNA-DNA hybridization: the samples were boiled for 10 min. and neutralized using 0.…”
Section: Microbiological Proceduresmentioning
confidence: 99%
“…The samples were analyzed for 40 oral bacterial species using the Checkerboard DNA-DNA Hybridization technique. 28,29 c. Checkerboard DNA-DNA hybridization: the samples were boiled for 10 min. and neutralized using 0.…”
Section: Microbiological Proceduresmentioning
confidence: 99%
“…6 Two subjects, one from the test group and one from the control group, reported adverse events (diarrhoea and vomiting) during the study. No statistically significant differences were observed between the groups with regard to the number of subjects reporting adverse events.…”
Section: Resultsmentioning
confidence: 99%
“…Another point in the studies analyzed concerns the changes in microbiological profile provided by amoxicillin + metronidazole. Valenza et al 37 found no change in the subgingival microbiota of patients with AP after 12 months, however, most of the studies relates a favorable change in the microbiological profile of patients who use these antimicrobial association [38][39] . In addition, all report favorable clinical results (no control group) or better than conventional treatment [38][39] .…”
Section: Antibioticsmentioning
confidence: 99%
“…Valenza et al 37 found no change in the subgingival microbiota of patients with AP after 12 months, however, most of the studies relates a favorable change in the microbiological profile of patients who use these antimicrobial association [38][39] . In addition, all report favorable clinical results (no control group) or better than conventional treatment [38][39] . When this association (amoxicillin + metronidazole) was compared with another protocol (doxycycline), both provided improvement in clinical and microbiological parameters in 3 months follow-up 40 .…”
Section: Antibioticsmentioning
confidence: 99%